Novel Rod-Shaped Magnetotactic Bacteria Belonging to the Class Alphaproteobacteria - Zhang, Wen-Yan (American Society for Microbiology, 2013)
Novel large, rod-shaped magnetotactic bacteria (MTB) were discovered in intertidal sediments of the Yellow Sea, China. They biomineralized more than 300 rectangular magnetite magnetosomes per cell. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that they are affiliated with the Alphaproteobacteria and may represent a new genus of MTB.